PENERAPAN TEORI THREE MATCH CUT DALAM PENGEDITAN BRAND GENERATED CONTENT (BGC) PADA AKUN TIKTOK @KITA_KELANA - Kurniawan, Ervan Muhammad Putra; Supama Wijaya, Abung (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
The evolution of TikTok as a digital communication platform has prompted brands to adopt storytelling-based brand generated content (BGC) through a soft-selling approach. In the realm of short-form video production, continuity editing is crucial for ensuring viewer comfort. This study seeks to develop an editing workflow grounded in the Three Match Cut theory for TikTok content on the @kita_kelana account, serving as a digital communication medium for the Kita Kelana brand. The research employed a practice-based approach with a qualitative descriptive method, involving the direct participation of the author as a video editor during the post-production phase. The editing workflow comprised stages of acquisition, organization, review and selection, assembly, rough cut, fine cut, picture lock, finishing, rendering, and export. The application of the Three Match Cut theory encompasses matching the look, position, and movement. The findings indicate that the implementation of the Three Match Cut effectively maintains visual continuity, clarifies spatial orientation and movement, fosters a more natural storytelling rhythm, and enhances audience viewing comfort. Continuity editing also facilitates the integration of brand messages into storytelling through a soft-selling approach. Consequently, a three-match cut-based editing workflow can function as a pertinent visual communication strategy in the production of Brand Generated Content on short-video platforms such as TikTok.